Non traumatic transfemorl amputation in critically ill patient – a case report - Rekhi, Balwinder Kaur; Grewal, Tejinderpal Kaur; Soni, Sumit; Kaur, Mandeep; Duvedi, Shuchi; Garg, Diksha; Kaur, Lovepreet (GMC Patiala Journal of Research and Medical Education, 2022)
Non traumatic transfemoral amputation is associated with considerable morbidity and mortality. Patients who are posted for emergency operative procedure, such as non-traumatic above knee amputation, generally present with comorbidities such as cardiac disorders, diabetes and peripheral vascular disease. There is significant lack of data describing the use of particular safe anesthetic approach. Here we present a case having multiple comorbidities to be taken up for Above Knee Amputation (AKA).